Characteristics and treatment outcomes of children and adolescents accessing treatment in Child and Youth Mental Health Services. Issue 12 (3rd February 2022) - Lu, Zhen Qi; de Geus, Hanna; Roest, Sanna; Payne, Leanne; Krishnamoorthy, Govind; Littlewood, Robyn; Hoyland, Margaret; Stathis, Stephen; Bor, William; Middeldorp, Christel M.
Abstract: Aim: To provide insight into the characteristics and treatment outcomes of children and adolescents accessing outpatient Child and Youth Mental Health Services (CYMHS), and to explore whether outcomes differ by age, sex, and ancestry background. This information can guide how to optimize the treatment delivered at these services. Methods: An observational retrospective study was performed based on data from 3098 children and adolescents between age 5 and 18 who received treatment at Brisbane, Australia, community CYMHS between 2013–2018. Patient characteristics, service use, and clinician and parent rated Routine Outcome Measures (ROM) were extracted from electronic health records. Results: Anxiety and mood disorders were the most common mental disorders (37% and 19%). In 1315 children and adolescents (42%), two or more disorders were diagnosed, and the far majority (88%) had experienced at least one psychosocial stressor. The ROM scores improved between start and end of treatment with Cohen's d effect sizes of around 0.9. However, 50% of the children still scored in the clinical range at the end of treatment. Outcomes did not differ over gender and Indigenous status. Conclusions: Children and adolescents accessing CYMHS have severe and complex mental disorders as reflected by high rates of comorbidity, exposure to adverse circumstances and high symptom scores at the start of treatment. Despite the clinically relevant and substantial improvement, end ROM scores indicated the presence of residual symptoms. As this increases the risk for relapse, services should explore ways to improve treatment to further reduce mental health symptoms.